Symbolic Interaction in Live Shopping: Consumption Ethics and Green Marketing from a Sustainability Accounting Perspective - Jannah, Miftahul; Fitriani, Fitriani; Alimuddin, Alimuddin; Said, Darwis (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze how symbolic interactions in live shopping on digital platforms shape consumer perceptions of product value, consumption ethics, and the credibility of sustainability claims conveyed through green marketing narratives. This study uses a qualitative approach with a non-positivistic paradigm and Blumer's symbolic interaction theory. Data were collected through virtual observation, in-depth interviews, and analysis of digital documentation to understand the meaning construction that emerged in real-time interactions between hosts and audiences. The results show that digital symbols, such as “eco-friendly” and “best seller” labels and sustainability narratives, play an important role in shaping consumer perceptions and purchasing decisions. However, the findings also reveal that many sustainability claims lack factual support, thereby increasing the risk of greenwashing. In addition, the study identifies an ethical consumption paradox: consumer sustainability awareness often fails to align with purchasing decisions due to social pressure, emotions, and the urgency created by the platform. This study emphasizes the importance of integrating sustainability symbols and transparent accounting evidence through ESG reporting, environmental audits, and digital disclosure innovations to increase public trust and encourage ethical and sustainable consumption practices.